Pengaruh Income Smoothing, Konservatisme Akuntansi, dan Informasi Laba terhadap Koefisien Respon Laba - Ahalik, Ahalik; Christian, Kelvin (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2020)
This research aims to analyze the influence of income smoothing, conservatism accountancy, and earnings informastion towards earnings response coefficient. The population in this research are all of the manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2015 - 2017. The sample selection by using purposive sampling and obtain a sample of 78 companies or 234 observation data. The data analysis method used in this multiple regression analysis by using SPSS version 24. The simultaneously result showed that income smoothing, conservatism accountancy and earnings information with simultaneously affect to earnings response coefficient. The partially result showed that conservatism accountancy affect negatively to earnings response coefficient while income smoothing and earnings information do not affect to earnings response coefficient.